Presence of Helicobacter pylori and H. suis DNA in free-range wild boars - Nunes, Francisco Cortez (2021)
Helicobacter pylori (H. pylori) is a Gram-negative bacterium that infects half of the human population worldwide, causing gastric disorders, such as chronic gastritis, gastric or duodenal ulcers, and gastric malignancies. Helicobacter suis (H. suis) is mainly associated with pigs, but can also colonize the stomach of humans, resulting in gastric pathologies. In pigs, H. suis can induce gastritis and seems to play a role in gastric ulcer disease, seriously affecting animal production and welfare. Since close interactions between domestic animals, wildlife, and humans can increase bacterial transmission risk between species, samples of gastric tissue of 14 free range wild boars (Sus scrofa) were evaluated for the presence of H. pylori and H. suis using PCR. Samples from the antral gastric mucosa from two animals were PCR-positive for H. pylori and another one for H. suis. These findings indicate that these microorganisms were able to colonize the stomach of wild boars and raise awareness for their putative intervention in Helicobacter spp. transmission cycle.